Acupuntura a laser no tratamento da dor crônica cervical - ensaio clínico randomizado - Vieira, Natália De Sousa Esteves (2022)
Introduction: Neck pain and low back pain are the two main causes of years lived with a disability, neck pain is the main cause of suffering and disability, so it is necessary to investigate the effects of treatments for this condition. Laser acupuncture has been used as one of the options for treating chronic cervical pain. Objectives: To validate a laser acupuncture treatment protocol for chronic neck pain and to evaluate the effect of laser on chronic neck pain. Methods: 1st stage consisted of a validation study of an instrument for neck pain. Then, this protocol was presented by e-mail to 44 experts in the subject and was answered by 21 of them. The 2nd stage consisted of a randomized clinical study carried out at the Universidade do Sudoeste Paulista - UNIFSP, approved by the Ethics Committee on Research with Human Beings (CAAE 44801021.0.0000.5373) and registered on the REBEC Clinical Trials Platform (RBR- 8mfwcwf). Twenty volunteers with chronic neck pain from the waiting list of the Physiotherapy Clinic at UNIFSP were recruited, as well as civil servants, students and employees. The volunteers were submitted to three assessments, a pre-treatment assessment (A1); an evaluation after 10 treatment sessions (A2), and 15 days after the end of treatment (A3). The variables analyzed were pain intensity, using the Numerical Pain Scale; physical disability, using the Roland Morris Disability Questionnaire; neck pain disability, by the Neck Related Disability Index (NDI) and the pain threshold by the digital algometer. Volunteers were randomized using the Randomizer.org program and divided into two groups: Group 1, which received 10 laser sessions at acupuncture points, and Group 2, control, which received no intervention. The laser used was the brand DMC® Therapy XT, in the acupuncture points bilaterally VB20, B10 (2J/cm2), B34, VG14, ID3, IG4 (4J/cm2) and the CG received postural guidance by image via WhatsApp®. The treatment was carried out twice a week for 5 weeks. Results: The evaluation of the protocol by expert evaluators resulted in an 80% agreement level of approval in all items. In the clinical trial, a decrease in physical disability was observed in GI (p=0.001) at the A1xA2 moment (p<0.001) and remained at A1XA3 ((p<0.001) in the inter-group comparison there was a decrease in reassessment (p=0.002), in cervical disability there was a decrease in GI (p<0.001) in A1xA2 (p<0.001) in the intergroup analysis A2 (p=0.028). In the analysis with algometer no statistically significant difference was observed regarding the increase in the cervical pain threshold in the pain assessment there was a significant decrease in both groups, GI (p<0.001) and GC (p=0.029) observing this decrease between A1XA2 (p=0.040). pain threshold increase Conclusion: The laser acupuncture treatment protocol for chronic neck pain was valid Laser acupuncture was effective in decreasing physical disability and decreasing neck pain disability and pain intensity.